Gaya Komunikasi Anas Urbaningrum Ditinjau Perspektif Kesantunan Berbahasa - Jusrin Efendi Pohan; Maulina, Intan (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2024)
A leader's communication skills are currently essential to realize organizational goals well. Processing language is a medium for conveying messages to organizational members. This is why this research describes the communication style of the national figure, General Chair of the Nusantara Awakening Party (PKN), Anas Urbaningrum, regarding language politeness. Anas Urbaningrum's elegant and charismatic style is reflected in every utterance spoken or written and can be categorized as polite. This research needs to be examined using the pragmatic theories of utterances that have been expressed. This research used a qualitative method that describes or describes a phenomenon by analyzing, reviewing, and concluding the data obtained. The primary data source for this research is the YouTube video of Anas Urbaningrum's resignation as chairman of the Democrats and statements made officially or unofficially. After the data is obtained, the data analysis step is carried out by reducing the data by selecting words to be interpreted. Analysis and study activities were conducted using listening techniques, such as listening to Anas Urbaningrum's statements on YouTube by transcribing the YouTube content first and then interpreting each sentence, paragraph, and discourse. This research indicates that Anas Urbaningrum's communication style can be categorized as an assertive communication style that uses language styles (terms) in delivery. No matter how great the political shock he suffered, Anas Urbaningrum still played connotative sentences that were embellished with other terms.